Initial experience with percutaneous mitral valve repair in patients with cardiac amyloidosis. (28th December 2020) - Volz, Martin J.; Pleger, Sven T.; Weber, Andreas; Geis, Nicolas A.; Hamed, Sonja; Mereles, Derliz; Hegenbart, Ute; Katus, Hugo A.; Frey, Norbert; Raake, Philip W.; Kreusser, Michael M.
Abstract: Background: Percutaneous mitral valve repair (PMVR) is a therapeutic option for severe mitral regurgitation (MR) in patients with heart failure due to differential aetiologies. However, only little is known about the safety and efficacy of this procedure in patients with amyloid cardiomyopathy. Methods: Five patients with cardiac amyloidosis and moderate to severe or severe MR undergoing PMVR were analysed retrospectively and compared to seven patients with cardiac amyloidosis and severe MR without intervention. Clinical and functional data, renal function and cardiac biomarkers as well as established risk scores for cardiac amyloidosis were assessed. Primary endpoint was the reduction in MR one year after PMVR. Secondary endpoints were safety, overall mortality after 12 months compared with the control group, as well as changes in clinical and functional parameters. Results: Amyloidosis risk assessment documented amyloid cardiomyopathy at an advanced stage in all patients. Procedural, technical and device success of PMVR were all 100% and residual MR remained mild to moderate at 12 months follow‐up ( P  = .038 vs before PMVR). Differences in survival compared with the control (no PMVR) group pointed to a possible survival benefit in the PMVR group ( P  = .02). Conclusion: PMVR is a feasible and safe procedure in patients with cardiac amyloidosis and might carry a possible survival benefit in this patient group.